Implications of stemness-related signaling pathways in breast cancer response to therapy. (April 2015) - Angeloni, Valentina; Tiberio, Paola; Appierto, Valentina; Daidone, Maria Grazia
Abstract: There is accumulating evidence that breast cancer may arise from a small subpopulation of transformed mammary stem/progenitor cells, termed breast cancer-initiating cells (BCICs), responsible for initiation and maintenance of cancer. BCICs have been identified in clinical specimens based on CD44 + /CD24 −/low membrane expression and/or enzymatic activity of aldehyde dehydrogenase 1 (ALDH1+), or isolated and in vitro propagated as non-adherent spheres. This cell population has been demonstrated to be able to recreate, when injected in mice even at very low concentrations, the same histopathological features of the tumor they were derived from and to escape from current therapeutic strategies. Alterations in genes involved in stemness-related pathways, such as Wnt, Notch, and Sonic Hedgehog, have been proven to play a role in breast cancer progression. Targeting these key elements represents an attractive option, with a solid rationale, although possible concerns may derive from the poor knowledge of tolerance and efficacy of inhibiting these mechanisms without inducing severe side effects. In addition, efforts to develop alternative BCIC-targeted therapies against stemness markers (CD44 and ALDH1) and molecules involved in regulating EMT- and HER2-related pathways, or able to reverse the multi-drug resistance phenotype, or to induce differentiation and to control cell survival pathways are currently ongoing and encouraging results from pre-clinical studies have already been obtained using in vitro and in vivo models.